RK-33, a small molecule inhibitor of host RNA helicase DDX3, suppresses multiple variants of SARS-CoV-2 - Vesuna, Farhad; Akhrymuk, Ivan; Smith, Amy; Winnard, Paul T.; Lin, Shih-Chao; Panny, Lauren; Scharpf, Robert; Kehn-Hall, Kylene; Raman, Venu (Frontiers in Microbiology, 2022)
SARS-CoV-2, the virus behind the deadly COVID-19 pandemic, continues to spread globally even as vaccine strategies are proving effective in preventing hospitalizations and deaths. However, evolving variants of the virus appear to be more transmissive and vaccine efficacy towards them is waning. As a result, SARS-CoV-2 will continue to have a deadly impact on public health into the foreseeable future. One strategy to bypass the continuing problem of newer variants is to target host proteins required for viral replication. We have used this host-targeted antiviral (HTA) strategy that targets DDX3, a host DEAD-box RNA helicase that is usurped by SARS-CoV-2 for virus production. We demonstrated that targeting DDX3 with RK-33, a small molecule inhibitor, reduced the viral load in four isolates of SARS-CoV-2 (Lineage A, and Lineage B Alpha, Beta, and Delta variants) by one to three log orders in Calu-3 cells. Furthermore, proteomics and RNA-seq analyses indicated that most SARS-CoV-2 genes were downregulated by RK-33 treatment. Also, we show that the use of RK-33 decreases TMPRSS2 expression, which may be due to DDX3s ability to unwind G-quadraplex structures present in the TMPRSS2 promoter. The data presented supports the use of RK-33 as an HTA strategy to control SARS-CoV-2 infection, irrespective of its mutational status, in humans.